Measles immunisation status of healthcare workers in smaller Victorian hospitals: can we do better?. (22nd July 2020) - Bennett, Noleen; Sutton, Brett; Strachan, Janet; Hoskins, Alex; Malloy, Michael J.; Worth, Leon J.
Abstract: Objective: To determine the proportion of healthcare workers (HCWs) in smaller Victorian public healthcare facilities with documented evidence of measles immunity. Methods: A cross‐sectional survey, developed by the Victorian Healthcare Associated Surveillance System Coordinating Centre, was completed by all eligible facilities. HCWs were reported as having evidence or no evidence of measles immunity. Those without evidence of immunity were sub‐classified as incomplete, declined or unknown status. Results: Seventy‐five facilities reported measles immunity status of 17, 522 employed HCWs. Of these, 11, 751 (67.1%) had documented evidence of immunity. The proportion with evidence of immunity was lowest (45.6%) in facilities with ≤50 HCWs. The majority of HCWs without evidence of immunity (88.2%) had 'unknown' status. Declination or incomplete status comprised very low overall proportions (0.3% and 3.6%, respectively). Conclusions: Reported evidence of HCW measles immunity was moderate in surveyed facilities, with a large proportion having unknown status. HCW immunisation programs in some facilities require refinement to appropriately support public health responses to measles cases and prevention of occupational acquisition of measles. Implications for public health: Non‐immune HCWs are at increased risk for acquiring and transmitting measles. Timely access to accurate HCW immunisation records is required to ensure that public health responses are effective.